All Days 2010
DOI: 10.2118/139641-ms
|View full text |Cite
|
Sign up to set email alerts
|

Retardation of CO2 due to Capillary Pressure Hysteresis: a New CO2 Trapping Mechanism

Abstract: Trapping of CO 2 improves containment security of geologically stored CO 2 . To be able to asses the potential of a storage site using reservoir simulators, it is necessary to include all of the possible trapping mechanisms in the numerical algorithms. Currently, four trapping mechanisms are identified in the CO 2 sequestration literature: structural, residual, dissolution, and mineralization. Although capillary pressure hysteresis has been accounted for in the historical development of simulators, it has not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…7 A variety of indirect effects, including plume evolution and residual capillary trapping, may also be linked to mobility. 52 Future petrophysical analyses for potential CO 2 sequestration sites should include relative permeability measurements on reservoir core samples rather than relying on extrapolations based on prior studies. Based on these results, CO 2 injectivity will be reduced and pressure-limited reservoirs will have reduced disposal capacity, though area-limited reservoirs may have increased capacity.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…7 A variety of indirect effects, including plume evolution and residual capillary trapping, may also be linked to mobility. 52 Future petrophysical analyses for potential CO 2 sequestration sites should include relative permeability measurements on reservoir core samples rather than relying on extrapolations based on prior studies. Based on these results, CO 2 injectivity will be reduced and pressure-limited reservoirs will have reduced disposal capacity, though area-limited reservoirs may have increased capacity.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Consequently, evaluation of seal capacity requires knowledge of the CO 2 -H 2 O capillary pressures. Residual fluid (gas or liquid phases) trapping refers to the retention of gaseous or liquid CO 2 in the aquifer pores due to a combination of hysteretic relative permeability Bennion and Bachu, 2006b, 2007Flett, et al, 2004;Juanes, et al, 2006;Liu, et al, 2004;Pentland, 2008;Spiteri et al, 2005) and capillary pressure effects (Alkan, et al, 2010;Altundas, et al, 2010;Bryant, et al, 2006;Juanes and MacMinn, 2008;Saadatpoor, et al, 2008Saadatpoor, et al, , 2009Saadatpoor, et al, , 2010b. Injection of gaseous CO 2 into an aquifer (continuous liquid phase) and followed by influx of additional water into the continuous CO 2 plume often creates a discontinuous, immobile CO 2 phase.…”
Section: Carbon Dioxide Trapping Mechanisms In Aquifersmentioning
confidence: 99%
“…Several studies have also investigated the impact of capillary heterogeneity on CO 2 movement and trapping in brine‐saturated porous media [ Hesse and Woods , 2010; Green and Ennis ‐ King , 2010; Mouche et al , 2010; Krause et al , 2011; Altundas et al , 2010; Perrin and Benson , 2009; Silin et al , 2009; Saadatpoor et al , 2009]. Using simulations and experiments with analogue fluids, Hesse and Woods [2010] and Green and Ennis ‐ King [2010] have shown that heterogeneity is important in determining the volume of residual trapping to the extent that it controls the volume of the reservoir that comes in contact with CO 2 .…”
Section: Introductionmentioning
confidence: 99%